PERISTILAHAN ALAT MEMERANGKAP BINATANG HUTAN PADA MASYARAKAT DAYAK JAWATN KECAMATAN SEKADAU HULU - Dona Agus Maria; Laurensius Salem; Patriantoro Patriantoro (Universitas Tanjungpura, 2018)
AbstractDayak Jawatn Society focused on terminologies of wild animal trapping tools using semantic analysis. The problems in this reserach are how is the terminologies’ inventory, lexical meaning, component analysis of semantic and function meaning. The methods used in this research is descriptive method. The form used is qualitative form. The data in this research is terminologies of wild animal trapping tools in Dayak Jawatn Society in the district of Sekadau Hulu. The data source in this research is Dayak Jawatn native speaker whose having knowledge of wild animal trapping tools and how to make it. The technique used in this research is listening technique that has advance stages: listening and speaking involvement technique, recording technique, and note technique. The tools used in collecting data are the researcher as key instrument and using supporting tools like interview instrument, sound recorder, camera, and stationery. Based on the research result Terminologies of Wild Animal Trapping Tools consist of six terminologies classification: 18 terms based on trap names, 3 terms based on tools, 5 terms based on materials, 14 terms based on parts, 25 terms based on process, and 4 terms based on places of putting the traps. Keywords: terminologies, wild animal trapping tools, Dayak Jawatn Society